Pusat Dukungan Odha DI Merauke (Pendekatan Arsitektur Modern) - Martinus Karpus Kora; Muchlis Alahudin; Biatma Syanjayanta (Musamus Journal of Architecture, 2020)
HIV / AIDS is a global problem. Statistical data on the number of people with HIV / AIDS in Merauke is increasing from (in 2010 to 2013). People with HIV / AIDS have not received adequate health care facilities and support. Meanwhile, discrimination against people with HIV / AIDS still applies in society. The purpose of this study is; (1) designing PLHIV Support Centers in Merauke that are equipped with supporting facilities, and (2) planning and designing precisely so that there is no discrimination against PLWHA with a Tropical Modern Architecture Approach.